Práticas pedagógicas no contexto das diferenças na alfabetização inicial - Santos, Simara Pereira dos (2013)
The purpose of the present research was to investigate how first year elementary school teachers conceive and organize the literacy process in order to attend to the differences present in the classroom. Theoretical support was provided by authors who investigated changes in literacy, teacher knowledge and the didactization of differences (MORTATTI, 2000, 2002; TARDIF, 2002, 2013; HUBERMAN, 2000; CANDAU, 2011, 2012; PERRENOUD, 2000, 2001, 2002). It has made it possible to carry out a retrospective of the paradigmatic changes and, consequently, the pedagogical practices present in Brazil during the last decades, from the thematizations, normalizations and concretizations in education; an analysis of teacher knowledge, its dimensions and representations; and the reflection on differences and the possibility of treating them methodologically. The methodological choice was a qualitative research of the Life History type, our interest in performing an analysis from the perspective of the teacher, seeking to apprehend the phenomenon in question from their perspective, making possible and evidencing the dimension of the processes and the construction of their skills to teach. Five teachers from the municipal network of the city of Salvador, Bahia, participated in the study. We had the following procedures for data collection: narrative interview, explanation interview and observation of written language classes. We used the Observation Scale of Differentiated Practices as reference for observation; with it, we identified the frequency of the strategies of differentiation in the daily practice of the teachers. The results indicate that teachers perceive the changes that have occurred in recent years regarding forms of literacy, they understand the need to build a practice favoring the didactization of differences, but they bump into contradictions and limitations when trying to articulate the theories that underlie this perspective in their practices. As historically situated subjects, they recognize the value of scientific knowledge in a pedagogical practice that meets the current demands. Nevertheless, they believe that practical and experiential knowledge are most relevant when teaching to read and write in this context. They classify the perception of students' differences into two groups: individual and social. They more easily develop didactic strategies that contemplate the first group. Observation based on the Observation Scale of Differentiated Pedagogical Practices has made it possible to realize that among the 79 differentiation strategies described therein, many were already part of the teachers' routine. We identified the presence of the strategies in the practice of teachers with greater or less regularity. Among three of the five teachers participating in the research, it was possible to observe a considerable number of strategies intentionally present. The other evaluated strategies appeared partially or barely. Among the other two teachers, although noticing some strategies present, many appeared little or partially, which led us to believe that the use of differentiation strategies emerged from the emergence of the situation, in an unplanned way most of the time. It seems to us that teachers differentiate independently of the conception they have, but those working more systematically in a so-called constructivist proposal differentiate with greater ownership and in a more conscious way.